Key research questions for a longitudinal survey of refugees and other humanitarian migrants - Khoo, Siew-Ean (My University, 2012)
This paper proposed that ‘Building a New Life in Australia: The Longitudinal Study of Humanitarian Migrants’ should focus on examining the changes that humanitarian migrants are likely to experience in their settlement process and the factors that contribute to these changes, particularly those that are relevant to settlement policy and programs. This focus is reflected in the discussion of the key research questions for the study.
Keywords: Culture -- Immigrants; Life Events -- Immigration / newly arrived migrants; Disadvantage, adversity and resilience; Life Events; Culture; Immigration / newly arrived migrants; Immigrants; Adversity and resilience; Dsiadvantage, adversity and resilience